Radical orthodoxy and protestantism today: John Milbank in conversation - J. Milbank (Acta Theologica, 2017)
This rough guide provides Prof. Milbank’s answers to questions from Sven Grosse for a conference, in German, held in Basel, Switzerland in 2017. This written interview will be published in German, but Prof. Milbank has kindly offered Acta Theologica the exclusive publication of this interview in English. It should be read along with the interview with Profs Milbank and Ward published in this Supplementum of Acta Theologica. What follows is not an ordinary academic paper. Instead, it is a polemical summary designed to give a general idea of Radical Orthodoxy (RO) in terms of its origins, main ideas, milieu and general cultural “feel”. If a great deal is mentioned about past thinkers and genealogies of the modern, it is not because RO thinkers suppose that this is at the heart of the modern, but rather because rival, liberal theological outlooks often, in part, depend, either openly or covertly, on stories about the past and the readings of some crucial thinkers. “Telling a different story” is then crucial to any genuinely subversive theological proposal. The majority of the stories I shall tell are based on scholarly research on RO, much thereof generally accepted by experts, if not always well disseminated. It is rather my “take” on these stories and their historical and contemporary implications that are most debatable and controversial.